Acute changes in strength and endurance performance and serum hormones to single session combined endurance and strength loadings : order effect in female and male endurance runners - Schumann, Moritz (2011)
Schumann, Moritz 2011. Acute changes in strength and endurance performance and serum hormones to single session combined endurance and strength loadings: Order effect in female and male endurance runners. Department of Biology of Physical Activity, University of Jyväskylä, Master’s thesis in Science of Sport Coaching and Fitness Testing, 76pp. Endurance and strength loadings are often performed concurrently by both elite and recreational athletes. The question of whether the order of exercise yields acute differences in force production and endocrine responses when both types of exercise are combined in a single session has, however, received only limited scientific attention. The purpose of this study was to examine acute changes and recovery in endurance and strength performance and serum hormone concentrations to single session combined endurance (E) and strength (S) loadings by switching the order of exercises in men and women. A group of 10 female (34±8 years) and 12 male (38±8 years) recreationally endurance trained subjects participated in the study. All subjects took part in two loading sessions; one with E loading followed immediately by S loading (E+S) and one with the opposite order (S+E). Prior to the measurements subjects were tested for their E (VO2max) and S performance (maximal bilateral isometric leg extension, MVCmax). The subjects then performed both loadings in a randomized order. S (45min) primarily focused on leg extensor muscles including both maximal and explosive exercises (3 x 8 reps with 75% of 1 RM and 3 x 10 reps with 40% of 1 RM with 2min rest between the sets) and E was performed as continuous running with intensity between lactic and ventilatory threshold (60min). MVCmax, rapid force production as average force of 500ms (MVC500) and serum hormone concentrations (total testosterone and cortisol) were determined PRE, MID (following E or S, respectively) and POST loadings and repeated after recovery of 24h and 48h. Oxygen consumption was measured during the first and last 10 minutes of the endurance loading and running economy was determined as the average of minutes 6-8 and 56-58. The main findings were significant decreases in MVCmax at MID and POST in men (MID, E+S, 8%, p<0.05; S+E, 19%, p<0.001; POST, E+S, 21%, p<0.001; S+E, 19%, p<0.00) in both loading conditions while these decreases were somewhat smaller in women (MID, S+E 14%, p<0.01; POST, E+S, 12%, p<0.01) Women did not show the same magnitude of reduction as men in MVC500 in both E+S and S+E). The recovery of MVCmax and MVC500 was faster in women, while in men reduced values were still observed at 48h of recovery following both loading conditions. Running economy was impaired in both men and women when endurance running was performed immediately after strength exercises (S+E). No significant changes occurred in serum testosterone in either men or women. During recovery serum testosterone at 24h and 48h of recovery was slightly decreased following S+E and slightly increased following E+S in men (at 24h, -14% vs. +7%, difference p<0.05; at 48h, -8% vs. +16%, difference p<0.05). Men showed slightly increased concentrations in serum cortisol (p=0.072) at POST following S+E compared to E+S. This increase in serum cortisol in men was higher (p<0.05) compared to unaltered serum cortisol concentrations in women. In conclusion, the present results showed that the current loading protocol led to higher neuromuscular fatigue and larger serum cortisol responses in men than in women, which were in part accompanied by decreased concentration of anabolic hormones during the recovery phase in men when the strength loading was followed by the endurance loading. These findings might have important implications to optimize the combined strength and endurance loading regimes and its order as well as recovery from loading in recreationally endurance trained males and females.